LANDLORD - TENANT, A BREACH OF A RESTRICTIVE COVENANT: DOES AN INTERLOCUTORY INJUNCTION LIE AGAINST A THIRD PARTY IN GOOD FAITH AND WITHOUT KNOWLEDGE? - Kaminsky, Howard (Revue de droit de l'Université de Sherbrooke)

(untitled) (Revue de Droit de l’Université de Sherbrooke, 1991)
This article attempts to examine the scenario of a breach of a restrictive covenant in a landlord-tenant situation, and deal with the question of whether an interlocutory injunction is the oppropriate remedy against a third party in good faith and without knowledge.In the introduction, the author will give an overview of the concept of injunctive relief in the province of Quebec and then focus on interlocutory injunctions.In the body of this work, the author will present conflicting jurisprudential opinions to the above mentioned question, and then present a recent decision.The author concludes by expressing his personal opinion in light of the said recent decision.